Portrayals of child and adolescent psychiatry in mass fiction: focusing on Stieg Larsson’s complete works - Pang, Nicholas (Research and Humanities in Medical Education, 2018)
Mass market fiction influences public perception of psychiatric services. Stieg Larsson’s "Millennium" crime fiction series is an absorbing one; however, the portrayal of child and forensic psychiatry in the trilogy is sensationalised and demonised, and compares poorly to the less paternalistic, more holistic, and more pedagogical-driven methods employed by contemporary child and adolescent services. This negative portrayal can lead to enacted public stigma, self stigma, and stigma from within the healthcare professions. This can adversely affect feelings, thoughts, behaviours and resource allocation towards psychiatry, and may also impair the self-esteem and adherence levels of people with psychiatric illness. There is a need for mass media to act as social watchdog, be an educational resource for long case histories, or serve to document contemporary perceptions of psychiatry. Anti-stigma movements, to counter the effect of negative media portrayal, should come from within psychiatry itself.